PENERAPAN METODE TEAM TEACHING DALAM PEMBELAJARAN MATEMATIKA DI SMA KRISTEN ABC SUKOHARJO [THE IMPLEMENTATION OF THE TEAM TEACHING METHOD IN LEARNING MATHEMATICS AT ABC CHRISTIAN HIGH SCHOOL IN SUKOHARJO] - Damanik, Remika Yulia Sari; Siahaan, Meri Fuji; Tamba, Kimura Patar (JOHME: Journal of Holistic Mathematics Education, 2018)
The team teaching method is a teaching method that is carried out by more than one teacher in a group of similar students by distributing their tasks, watching over them with one and another, evaluating the lesson, and complimenting each other to increase the learning outcomes of the students. The aims of this research was to analyze the implementation of the team teaching method in  mathematics learning at ABC Christian High School in Sukoharjo. Mathematics aims to deepen students' understanding of God's creation and how it helps them to fulfill their calling. The research was conducted from July 18, 2016, to November 4, 2016. The subjects were the vice principal, mathematics teachers, and 29 students. This research was a case study research about the implementation of the team teaching method in mathematics learning at ABC Christian High School in Sukoharjo. The research instruments used were interview and documents. The results showed that the implications of the team teaching method were a semi full team teaching, where the teacher teaches with a division of tasks, materials, and hours in learning mathematics. The team teaching method with material distribution and teaching hours helped to overcome the teachers' situation and the learning needs of mathematics at the school, but students found it difficult to follow the teaching team's method as they were studying two different topics in a week.BAHASA INDONESIA ABSTRAK: Metode team teaching adalah metode pembelajaran yang dilaksanakan oleh lebih dari satu orang guru pada sekelompok siswa yang sama dengan cara membagi tugas, bersama-sama mengamati siswa, mengevaluasi pengajaran dan saling mendukung untuk meningkatkan hasil belajar siswa. Tujuan penelitian ini untuk mengetahui penerapan metode team teaching dalam pembelajaran matematika di SMA Kristen ABC Sukoharjo. Matematika bertujuan untuk memperdalam pengertian siswa tentang ciptaan Allah dan bagaimana pengertian itu membantu mereka untuk memenuhi panggilan mereka. Penelitian dimulai sejak tanggal 18 Juli 2016 sampai 4 November 2016. Subjek penelitian yaitu wakil kepala sekolah bidang kurikulum, guru matematika sebanyak empat orang, dan siswa sebanyak 29 siswa. Penelitian ini merupakan penelitian kualitatif studi kasus tentang penerapan metode team teaching dalam pembelajaran matematika di SMA Kristen ABC Sukoharjo. Instrumen penelitian yang digunakan adalah wawancara, observasi sebanyak tujuh belas kali dan dokumen. Hasil analisis data menunjukkan bahwa metode team teaching yang diterapkan di SMA Kristen ABC Sukoharjo merupakan semi full team teaching, dimana guru mengajar dengan pembagian tugas, materi dan jam pada pembelajaran matematika. Metode team teaching dengan pembagian materi dan jam mengajar membantu mengatasi keadaan guru dan kebutuhan pembelajaran matematika di sekolah tersebut, namun siswa kesulitan mengikuti penerapan metode team teaching karena mempelajari dua topik yang berbeda dalam seminggu.